2016
DOI: 10.1038/gt.2016.29
|View full text |Cite
|
Sign up to set email alerts
|

Adenovirus-mediated hAQP1 expression in irradiated mouse salivary glands causes recovery of saliva secretion by enhancing acinar cell volume decrease

Abstract: Head and neck irradiation (IR) during cancer treatment causes by-stander effects on the salivary glands leading to irreversible loss of saliva secretion. The mechanism underlying loss of fluid secretion is not understood and no adequate therapy is currently available. Delivery of an adenoviral vector encoding human aquaporin-1 (hAQP1) into the salivary glands of human subjects and animal models with radiation-induced salivary hypofunction leads to significant recovery of saliva secretion and symptomatic relief… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
22
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 38 publications
(65 reference statements)
4
22
0
Order By: Relevance
“…It has been previously shown that by 60 days post-IR there is a reproducible chronic loss of saliva. 18 , 19 , 20 As expected, IR significantly reduced saliva secretion more than 50% compared with non-IR controls ( Figure 4 ), and treatment with the control vector (AdC+IR) did not improve saliva secretion. However, treatment with all three doses of AdNRTN before IR improved salivary secretion so that it was similar to non-IR control levels ( Figure 4 ).…”
Section: Resultssupporting
confidence: 74%
“…It has been previously shown that by 60 days post-IR there is a reproducible chronic loss of saliva. 18 , 19 , 20 As expected, IR significantly reduced saliva secretion more than 50% compared with non-IR controls ( Figure 4 ), and treatment with the control vector (AdC+IR) did not improve saliva secretion. However, treatment with all three doses of AdNRTN before IR improved salivary secretion so that it was similar to non-IR control levels ( Figure 4 ).…”
Section: Resultssupporting
confidence: 74%
“…Our present findings revealed that reduction of SOCE in acinar cells after irradiation could fully account for the impairment of salivary fluid secretion and that of agonist-stimulated decrease in acinar cell volume (31). We showed that this impairment of SOCE was due to loss of STIM1, which occurred downstream of caspase-3 activation.…”
Section: Discussionsupporting
confidence: 52%
“…Salivary gland irradiation was accomplished by placing each animal into a specially built Lucite jig such that the animal could be immobilized without the use of anesthetics. In addition, the jig was fitted with a Lucite cone that surrounded the head and prevented head movement during the radiation exposure (14, 31). Lead shields were designed to cover the jigs with the mice with a small aperture in the lead shield that allowed radiation to the salivary gland area of the immobilized animal.…”
Section: Methodsmentioning
confidence: 99%
“…Salivary glands play an essential role in oral health, and the reduction of saliva flow causes deterioration of the quality of life 55 . Previous studies have rescued the partial salivary gland function through the recovery of salivary production by stem cell transplantation or the over-expression of water-channel proteins 56 – 58 . We have proposed a concept of bioengineered salivary gland organ replacement, but not tissue repair, via the transplantation of a bioengineered germ in a mouse model of salivary defect 9 .…”
Section: Discussionmentioning
confidence: 99%